P501 Low prevalence of high-risk anal HPV in young gay and bisexual males after the universal HPV vaccination program in australia. (14th July 2019) - Chow, Eric; Tabrizi, Sepehr; Fairley, Christopher; Wigan, Rebecca; Cornall, Alyssa; Atchison, Steph; Machalek, Dorothy; Hocking, Jane; Bradshaw, Catriona; Garland, Suzanne; Chen, Marcus
Abstract : Background: Australia introduced a school-based quadrivalent human papillomavirus (HPV) vaccination program for females in 2007. This was extended to include boys aged 12–13 from 2013, with a two-year catch-up for boys aged ≤15. This study examined HPV prevalence among young gay and bisexual males (GBM) who were age-eligible for vaccination in the school-based program. Methods: Males aged 16–20 years were recruited from sexual health clinics and the community in Melbourne in 2017–2018, if they reported any form of male sexual contact, and were residents of Australia from 2013. A clinician-collected anal swab, self-collected penile swab and oral rinse were collected and analysed for detection and 37 HPV genotypes (Roche Linear Array). Preliminary results from 114 GBM were analysed and full results will be available for presentation. Results: The mean age of GBM was 18.6 years (SD 1.0). The majority (80%) were recruited from clinics and 20% from the community. The median number of lifetime male partners was 10 [IQR 5–25] for receptive oral sex, four [IQR 1–11] for receptive anal sex and one for insertive anal sex [IQR 0–6]. Overall, 64% received at least one dose of vaccine documented via the National HPV Vaccination Program Register. Prevalence of quadrivalent vaccine-preventable HPV genotypes was 4.9% (95% CI: 1.6–11%) for anal, 3.4% (95% CI: 0.7–9.5%) for penile and 0% (95% CI: 0–3.2%) for oral sites. Only two men, both unvaccinated, had high-risk vaccine-preventable HPV genotypes: one with anal HPV16 (1%); the other penile HPV16 (1%). Conclusion: Statistical analysis comparing before and after the male vaccination program will be performed until recruitment is completed. The preliminary analysis shows the prevalence of anal HPV 16/18 among young GBM following the school-based male HPV vaccination was low. The addition of male HPV vaccination to female programs may reduce the incidence of anal cancer among GBM. Disclosure: No significant relationships.